Association of metabolic syndrome with hypothyroidism and hyperuricemia: A cross-sectional study in a tertiary care hospital, Kolkata, West Bengal - Atanu Chakraborty; Amitabha Pal; Sudipta Pal; Saswati Mukherjee (Asian Journal of Medical Sciences, 2023)
Background: Metabolic Syndrome (MetS) (Syndrome X, insulin resistance syndrome, MetS) consists of a constellation of metabolic abnormalities which include central obesity, hyperglycemia, insulin resistance, high triglycerides, low high-density lipoprotein (HDL) cholesterol, and hypertension. Obesity is a critical component of MetS. It causes alteration in the thyroid hormones and hyperuricemia. Furthermore, insulin resistance seen in MetS causes decreased uric acid excretion.